Auditoría médica en el primer nivel de atención. - LLANOS ZAVALAGA, Fernando (Revista Médica Herediana, 2013)
We revised briefly: The origins of audit in the health sector and the historical variation of this concept. This concept has switched from a sanctional tool to a methodology of quality assurance and continuous quality improvement. International trends and the so called Evidence-based audit are also analized.